Testing the Role of Emotion Dysregulation as a Predictor of Juvenile Recidivism - Kalin Z. Salinas; Amanda Venta (MDPI AG, 2021)
The current study proposed to determine whether adolescent emotion regulation is predictive of the amount and type of crime committed by adolescent juvenile offenders. Despite evidence in the literature linking emotion regulation to behaviour problems and aggression across the lifespan, there is no prior longitudinal research examining the predictive role of emotion regulation on adolescent recidivism, nor data regarding how emotion regulation relates to the occurrence of specific types of crimes. Our primary hypothesis was that poor emotion regulation would positively and significantly predict re-offending among adolescents. We tested our hypothesis within a binary logistic framework utilizing the Pathways to Desistance longitudinal data. Exploratory bivariate analyses were conducted regarding emotion regulation and type of crime in the service of future hypothesis generation. Though the findings did not indicate a statistically significant relation between emotion regulation and reoffending, exploratory findings suggest that some types of crime may be more linked to emotion regulation than others. In sum, the present study aimed to examine a hypothesized relation between emotion regulation and juvenile delinquency by identifying how the individual factor of dysregulated emotion regulation may have played a role. This study's findings did not provide evidence that emotion regulation was a significant predictor of recidivism over time but did suggest that emotion regulation is related to participation in certain types of crime one year later. Directions for future research that build upon the current study were described. Indeed, identifying emotion regulation as a predictor of adolescent crime has the potential to enhance current crime prevention efforts and clinical treatments for juvenile offenders; this is based on the large amount of treatment literature, which documents that emotion regulation is malleable through treatment and prevention programming.